EFFECTS OF INVOLUTE SPUR GEAR STRUCTURE PARAMETERS ON MESHING EFFICIENCY - ZHANG BaoFeng; CUI YaHui; LIU Kai; Dong YaWen (Jixie qiangdu)
Based on the concept of contact counterforce between gear pair,the paper studied the meshing efficiency of involute spur gear mechanism,analyzed the effect factors of friction coefficient between contact tooth surfaces. Referring to the existent research models of friction coefficient,the paper discussed the meshing characteristics of spur gear and helical gear’s transmission,and derived the mathematic expressions of instantaneous meshing efficiency and average meshing efficiency for gear transmission of spur gear and helical gear. And then under the situation of different transmission ratios,pressure angles and friction coefficients,the paper analyzed the meshing efficiency of gear mechanism. The results show that friction coefficients are in inverse proportion to gear meshing efficiency,biggish pressure angles and transmission ratios contribute to improve gear meshing efficiency,and the meshing efficiency of increasing gear is higher than reducing gear.